2021
DOI: 10.1007/978-3-030-85610-6_16
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mobile and Virtual Reality Applications to Support Well-Being: An Expert View and Systematic App Review

Abstract: Interactive technologies for autonomous mental health management are on the rise due to limited therapy access and stigma. However, most commercial mental health apps are neither theory-based nor clinically tested, and psychological theories are not easily accessible to app designers. Thus, it remains unclear if current mobile and VR mental health apps meet therapists' expectations. To address this gap, we conducted interviews (N = 11) to build an understanding about current therapeutic practices with a focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…[44,83]). On a similar note, a recent review of commercial VR well-being apps found that only one app offered the possibility to (partly) autonomously design the environment [84]. Other designers fostered autonomy by actively engaging participants during the design process of a VE, but the design could not be further adjusted after entering the VE [28].…”
Section: Technologies For Well-beingmentioning
confidence: 99%
See 4 more Smart Citations
“…[44,83]). On a similar note, a recent review of commercial VR well-being apps found that only one app offered the possibility to (partly) autonomously design the environment [84]. Other designers fostered autonomy by actively engaging participants during the design process of a VE, but the design could not be further adjusted after entering the VE [28].…”
Section: Technologies For Well-beingmentioning
confidence: 99%
“…Other designers fostered autonomy by actively engaging participants during the design process of a VE, but the design could not be further adjusted after entering the VE [28]. However, research suggests that the process of autonomously designing VEs is therapeutic in itself [84] and that emotional content should be adjusted in real-time [59].…”
Section: Technologies For Well-beingmentioning
confidence: 99%
See 3 more Smart Citations